2023
DOI: 10.3389/fnhum.2023.1092154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of additive sensory noise on cognition

Abstract: BackgroundAdding noise to a system to improve a weak signal’s throughput is known as stochastic resonance (SR). SR has been shown to improve sensory perception. Some limited research shows noise can also improve higher order processing, such as working memory, but it is unknown whether SR can broadly improve cognition.ObjectiveWe investigated cognitive performance while applying auditory white noise (AWN) and/or noisy galvanic vestibular stimulation (nGVS).MethodsWe measured cognitive performance (n = 13 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This is furthered by a recent investigation which observed mixed results for AWN and cognition in neurotypical subjects (Awada et al, 2022). Further, research conducted by our lab found no broad cognitive enhancements under sensory noise, but found that subject interactions were significant, with subjects that self-reported being able to work better with background noise showing cognitive enhancement as a result of sensory noise treatment (Sherman et al, 2023a). This implies that applying sensory noise for cognitive processing may only be beneficial for certain individuals.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…This is furthered by a recent investigation which observed mixed results for AWN and cognition in neurotypical subjects (Awada et al, 2022). Further, research conducted by our lab found no broad cognitive enhancements under sensory noise, but found that subject interactions were significant, with subjects that self-reported being able to work better with background noise showing cognitive enhancement as a result of sensory noise treatment (Sherman et al, 2023a). This implies that applying sensory noise for cognitive processing may only be beneficial for certain individuals.…”
Section: Discussionsupporting
confidence: 47%
“…Along this notion, sensory noise has been shown to improve elements of cognition, such as working memory (Wilkinson et al, 2008;Söderlund et al, 2010). Further, previous research conducted in our lab showed that certain individuals may show comprehensive cognitive improvement (Sherman et al, 2023a). This evidence implies that SR could be useful for improving information processing.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation